A Macro-Financial Perspective to Analyse Maturity Mismatch and Default - Xuan Wang (Tinbergen Institute, 2020)
The Basel Committee proposed the Net Stable Funding Ratio (NSFR) to curb excessive maturity mismatch of the banking sector. However, it remains to be ascertained as to what are the financial and real effects of the NSFR on banks' credit quality, investment, and the pass-through of monetary policy. This paper develops a nominal dynamic general equilibrium featuring banks' maturity mismatch and the moral hazard due to costly monitoring. First, I show that a tightening of the NSFR to move loan maturity towards the long-run capital investment cycle would only increase real investment if it sufficiently improves banks' credit quality. Then in the numerical example calibrated with the US data, I show that such tightening of the NSFR can indeed increase real investment and also reduce the aggregate fluctuation of the economy. In the steady states, a 10% tightening in the NSFR can decrease net charge-offs of non-performing loans by about 0.06 pp annually, despite squeezing banks' interest margin. Moreover, the moral hazard stemming from banks' unobserved monitoring effort impairs the pass-through of monetary policy. However, a 10% tightening in the NSFR improves the pass-through of a 20-bp policy rate reduction by around 17% annually. Finally, the model simulates the stochastic dynamic equilibrium path to study the propagation of shocks, demonstrating that the NSFR complements monetary policy in reducing financial frictions.
Keywords: E44; E51; G18; G21; 330; Maturity mismatch; Net Stable Funding Ratio; default; banking; monetary policy; macro-prudential policy